Design of Multi-hop Qos Scheduling for IEEE 802.16 Networks - Yi-Ting Mai; Chun-Chuan Yang; Jeng-Yueng Chen; Cheng-Jung Wen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Broadband wireless networks are increasing in popularity owing to current advances in technology. For large area network deployment, IEEE 802.16 mesh networks can provide a wide coverage, high speed and high quality multimedia service. IEEE 802.16 mesh configuration eliminates the need to have direct links between subscriber stations (SSs) and the base station (BS); a node can choose the links and path of the highest quality to transmit data and avoid the congested areas. To provide better Quality of Service (QoS) over the 802.16 network, the network layer 3 (L3) and layer 2 (L2) QoS must be integrated. Hence, cross-layer mechanisms were designed and incorporated into our previously proposed IEEE 802.16 QoS frameworks. Taking into consideration resource utilization and QoS requirements, we devised various scheduling schemes to determine their effects on the IEEE 802.16 mesh network. Our performance evaluation demonstrates that the proposed framework with enhancement scheduling has higher throughput, lower delay and signal cost than comparable systems. In this paper, we provide an appraisal of our proposed scheme. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3708